Batman, the brave and the bold. The complete season three [videorecording (Blu-Ray)] - DeMatteis, J. M. (Warner Home Video, 2017)
Join the Caped Crusader and a wealth of DC's finest as they team up to battle injustice in the third and final season of this cutting-edge series! Evil never sleeps in these diabolical schemes plotted by the world's most infamous criminals including the Joker, Lex Luthor, Equinox and Ra's Al Ghul! Thankfully, Batman and his many allies, including Superman, Green Lantern, Aquaman and Wonder Woman, are always up for the challenge!